Faktor-Faktor yang Mempengaruhi Penerapan Keterlibatan Karyawan pada Industri Manufakturing - Alden Nelson (Journal of Global Business and Management Review, 2019)
The research conducted to discuss the factors that affecting the implementation of employee engagement. Employee engagement contributes to companies where low turnover, high profitability and high productivity. The results of the study explained the direct effect that leadership, teamwork, management support had a significant effect to employee motivation and employee development / training, environment / workplace, teamwork, management support, employee motivation directly influencing to employee engagement but performance management, compensation / remuneration leadership does not have a significant effect to employee engagement. Indirect influence explains that leadership and team work have a significant effect to employee engagement through employee motivation but management support does not significantly influence employee engagement through employee motivation.